Case Report: Dengue Hemorrhagic Fever in Children - Maria Wahyu Daruki (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Patients came to the Puskesmas with the patient's child with complaints of heat for 4 days ago before the patient went to the Puskesmas. The patient began to feel the body shivering for 4 days ago by feeling pain throughout the body accompanied by shivering and not having energy/feeling weak. At present, patients complain of headaches, joints ache and feel just want to stay alone. The patient checked the patient's temperature around 38-39˚C for 2 days ago. The patient did not complain of swallowing pain, decreased appetite, but the patient still ate a lot to improve the condition. The heat arises suddenly during the day, and the patient only takes the drug paracetamol but the heat and pain decrease only slightly. Patients had had time to go to the Puskesmas and check blood at that time obtained 138,000 platelet laboratory results, hematocrit 46.7% and leukocyte rate 3,200/mm3, the patient was given medication by a doctor at the Puskesmas paracetamol 3x500 and vitamin C, and recommended control again the next day. At the time of control, the patient's condition was still weak, headache was still persistent, and also joint pain was still present. Then blood was taken again, and platelet results were obtained 70,000/μl, hematocrit 70.1% and leukocyte count 6,500/mm3, around the patient's home there was 1 child who was treated with dengue fever. The patient complained of nausea but did not vomit. The gums are not bleeding and there are no nosebleeds, then an RL test and a positive result are performed. Patients are advised to be referred to Regional Public Hospital to get further treatment. The patient has never experienced this condition before. The patient had typhus but was not hospitalized, only with outpatient care. Other illnesses are just coughing and the common cold, not serious illnesses. The patient has a drug allergy to ciprofloxacin.